Psychological Influence on Nurses' Behavior in Carrying Out Caring for Stroke Patients at the Nganjuk Regional General Hospital - Sujatmiko (Saniya Institute, 2023)
Stroke is one of the main causes of death and neurological disability in Indonesia. This brain attack is a medical emergency that must be treated quickly, precisely and carefully. Several efforts can be made to improve caring behavior, namely by increasing nurses' understanding of caring, providing social support as physical and psychological comfort from friends and hospital management in increasing caring for stroke patients. This research method uses correlational analytical research. The results of this study state that nurses' psychological factors have an influence on nurses' caring behavior.